Electrochemical synthesis, characterization and capacitive properties of novel thiophene based conjugated polymer - Celik, Burcu; Celik, Ilharni; Dolas, Hacer; Gorcay, Hakan; Sahin, Yucel; Sarac, A. Sezai; Pekmez, Kadir (ELSEVIER, 2014)
In this paper, a novel thiophene based monomer, 1-(pyren-1-yl)-2,5-di(thiophen-2-yl)-1H-pyrrole, PThP, was synthesized and characterized by H-1 NMR and C-13 NMR spectroscopic methods. The electrochemical behavior and electropolymerization of this novel monomer were performed on pencil graphite electrode (PGE) by cyclic voltammetry. The effect of solvent, dopant, scan number and scan rate on the electropolymerization and properties of the conjugated polymer films were investigated. The capacitive properties of the poly(PThP) films were tested by electrochemical impedance spectroscopy (EIS). The highest specific capacitance value was calculated for the conjugated polymer modified PGE that was obtained in 0.1 M tetrabutylammonium perchlorate/dichloromethane solution for 30 cycles at 25 mV/s scan rate as 25.45 mF cm(-2). The surface morphologies of the conjugated polymer modified electrodes were determined by scanning electron microscopy (SEM). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thiophene; Cyclic voltammetry; Electropolymerization; Electrochemical impedance spectroscopy; Supercapacitor; IMPEDANCE CHARACTERIZATION; ELECTRODE MATERIALS; SURFACE-MORPHOLOGY; POLYANILINE; Chemistry; Engineering; Polymer Science